2014
DOI: 10.1213/ane.0000000000000438
|View full text |Cite
|
Sign up to set email alerts
|

Fall-Prevention Strategies and Patient Characteristics That Impact Fall Rates After Total Knee Arthroplasty

Abstract: Our data demonstrate a reduction in fall incidence coinciding with the implementation of a multi-intervention fall-prevention strategy. Despite prevention efforts, patients of advanced age, elimination-related activities, and patients in the intermediate phase (late postoperative day 1 through day 3) of recovery continue to have a high risk for falling. Therefore, fall-prevention strategies should continue to provide education to all patients (especially elderly patients) and reinforce practices that will moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 24 publications
3
25
0
4
Order By: Relevance
“…Similarly, Delbaere et al (2010) emphasised that older patients with impaired balance have a considerable risk of falls. Johnson et al (2014) reported that most elimination-related falls frequently occurred in the bathroom. Therefore, clinicians should more carefully monitor inpatients with the risk factors identified in this study to ensure patient safety and effectively prevent falls.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Delbaere et al (2010) emphasised that older patients with impaired balance have a considerable risk of falls. Johnson et al (2014) reported that most elimination-related falls frequently occurred in the bathroom. Therefore, clinicians should more carefully monitor inpatients with the risk factors identified in this study to ensure patient safety and effectively prevent falls.…”
Section: Discussionmentioning
confidence: 99%
“…89 In the context of an accelerated TKR pathway, concerns have been expressed about inability to ambulate on the day of operation after an additional SNB. 90,91 Remarkably, no delay in discharge or functional outcome was found when SNB was combined with FNB. 76,82 Ambulation on the first postoperative day after SNB was significantly impaired in some patients compared with local infiltration techniques of the posterior capsule but did not differ from the second postoperative day until discharge.…”
Section: Sciatic Nerve Block For Tkamentioning
confidence: 97%
“…. Une revue sur une période de 10 ans a précisé les circonstances de chute après prothèse de genou [27]. En dépit des stratégies de pré-vention mises en place, les chutes survenaient le plus souvent entre les premier et troisième jours postopératoires.…”
Section: Risque De Chuteunclassified
“…Cependant, après analyse d'un collectif de près de 2200 prothèses de genou, il n'était pas retrouvé d'augmentation du risque de chute pour un bloc fémoral ou un bloc sciatique en injection unique [10]. La population à risque de chute peut être mieux définie et concerne le type de chirurgie [25,26] (prothèse de genou et reprise de prothèse de hanche ou de genou), les antécédents de chute [37], le sujet âgé [25,27,32,33], l'obèse [32,33], pour certains le sexe féminin [26] ou pour d'autres le sexe masculin [25,33] et le cathéter périnerveux fémoral [26,[30][31][32]. Les mécanismes responsables de la chute lors de l'association de blocs du membre inférieur sont la diminution de la rigidité du membre et l'instabilité latérale dans les manoeuvres de pivotement [34] [30].…”
Section: Risque De Chuteunclassified
See 1 more Smart Citation